The Strategy of the Kajang Ammatoa Traditional Community in Maintaining the Pasang ri Kajang in the Globalization Era - A. Devi Tenri Puji; Sakaria Sakaria; Nuvida RAF; Suaib Suaib (YASIN, 2026)
Globalization has intensified information flows, modernization, and social interactions, creating both opportunities and challenges for the preservation of local customary values. Within this context, the Kajang Ammatoa indigenous community in Tana Towa Village, Bulukumba Regency, Indonesia, continues to uphold Pasang ri Kajang as a normative guide governing human relationships with others, nature, and the Creator. This study aimed to analyze the socio-cultural impacts of globalization on the community and to examine the strategies employed to preserve Pasang ri Kajang values amid ongoing social change. The research adopted a qualitative case study approach, with data collected through field observations, in-depth interviews with customary leaders and knowledgeable community members, and document analysis. The findings indicate that globalization has encouraged gradual social adaptation without directly eroding the community’s core values. The principal preservation strategies include strengthening the authority of customary institutions, maintaining a simple way of life through Kamase-masea, and transmitting values through everyday social practices. The study also found that the community selectively adapts modern elements while remaining anchored to its foundational norms. Interpreted through Anthony Giddens’ structuration theory, Pasang ri Kajang functions as a normative structure that is continuously reproduced and negotiated by social agents through reflexive practice. The study concludes that cultural continuity within the Kajang Ammatoa community is dynamic rather than static, sustained through reflective adaptation that enables Pasang ri Kajang to remain relevant amid globalization. These findings contribute to the understanding of indigenous cultural resilience and demonstrate how customary communities preserve core values while negotiating contemporary social transformations.